2021
DOI: 10.1177/17562848211024769
|View full text |Cite
|
Sign up to set email alerts
|

The real-world outcomes of vedolizumab in patients with ulcerative colitis in Korea: a multicenter retrospective study

Abstract: Aim: This study examined the real-world effectiveness and safety outcomes of vedolizumab in ulcerative colitis (UC) patients who had failed anti-tumor necrosis factor (anti-TNF) therapy in Korea. Methods: A retrospective chart review study was conducted in adults with moderate to severely active UC who had failed anti-TNF agents and subsequently received vedolizumab. Clinical response and clinical remission at week 6 and 14 after vedolizumab initiation was evaluated. Safety outcomes were also reported. Outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…A post hoc analysis of GEMINI 1 [ 10 ], the pivotal clinical trial of vedolizumab in patients with UC, demonstrated significantly higher clinical response rates after vedolizumab induction at week 6 in both TNFα inhibitor-naïve (53.1%) and TNFα-experienced patients (39.0%) as compared with placebo in TNFα inhibitor-naïve (26.3%) and TNFα-experienced patients (20.6%). In a Korean real-world study of patients with UC whose disease had to failed to respond to TNFα inhibitor therapy, the week 6 clinical response rate was 51.1% in GEMINI 1–matched subjects [ 12 ]. A phase 3 clinical trial of vedolizumab in Japanese patients also showed a significantly higher clinical response rate at week 10 in TNFα inhibitor-naïve patients (53.2%) in comparison with placebo controls (36.6%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A post hoc analysis of GEMINI 1 [ 10 ], the pivotal clinical trial of vedolizumab in patients with UC, demonstrated significantly higher clinical response rates after vedolizumab induction at week 6 in both TNFα inhibitor-naïve (53.1%) and TNFα-experienced patients (39.0%) as compared with placebo in TNFα inhibitor-naïve (26.3%) and TNFα-experienced patients (20.6%). In a Korean real-world study of patients with UC whose disease had to failed to respond to TNFα inhibitor therapy, the week 6 clinical response rate was 51.1% in GEMINI 1–matched subjects [ 12 ]. A phase 3 clinical trial of vedolizumab in Japanese patients also showed a significantly higher clinical response rate at week 10 in TNFα inhibitor-naïve patients (53.2%) in comparison with placebo controls (36.6%).…”
Section: Discussionmentioning
confidence: 99%
“…However, response to treatments for UC may vary across ethnic populations [ 8 ]. Although a study in Korea reported real-world effectiveness and safety outcomes of vedolizumab in patients with UC [ 12 ], post-marketing surveillance data for vedolizumab in Japanese patients is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study examined the real-world effectiveness and safety outcomes of vedolizumab in patients with UC who had failed anti-TNF therapy in Korea ( Ye et al, 2021 ). The study included 105 patients and authors found that within the first 14 weeks of use, vedolizumab is effective and well tolerated in the real-world setting.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the favourable efficacy and safety profiles of VDZ in Asian IBD populations 13–17 and have identified a similar pharmacokinetic profile of VDZ between Asian and non‐Asian patients with moderately‐to‐severely active CD and UC 18 . Nonetheless, uncertainty remains regarding whether these CDSTs can be effectively utilised in Asian populations in real‐world practice.…”
Section: Introductionmentioning
confidence: 99%